STUDY OF MAKING HYDROLYSIC OF LOMEK FISH PROTEIN (Harpodon nehereus) USING PAPAIN ENZYMES - Muhammad Iqbal; Suparmi Suparmi; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This study aims to determine the quality of lomek fish protein hydrolyzate and characteristics with the addition of papain enzymes. The method used is the experimental method with the experimental design used is a non-factorial Complete Complete Design (CRD) with 3 replications consisting of 3 treatments, namely the addition of papain enzyme 10% (L1), 15% (L2), and 20% (L3 ) The parameters observed were proximate (moisture content, ash, fat, protein) and total amino acid analysis. The results showed that the addition of 20% papain enzyme was the best treatment with chemical composition namely water content 91.08% bb, ash content 0.37% bk, protein content 80.60% bk, and fat content 0.20% bk. Lomek fish protein hydrolyzate has 15 types of amino acids consisting of 9 essential amino acids and 6 types of non-essential amino acids. Lomek fish hydrolyzate protein contains 9 types of essential amino acids including valine, methionine, threonine, leucine, phenylalanine, histidine, lysine, isoleucine, and arganin. While the non-essential amino acids contained in the lomek fish protein hydrolyzate consist of 6 types, namely, aspartic acid, serine, glutamic acid, glycine, alanine, and tyrosine. Keywords: Amino acids, enzymes, hydrolyzate,proximate,